Electronically tunable floating CMOS resistor using OTA - Kaewdang, Khanittha; Kumwachara, Kiattisak; Surakampontorn, Wanlop (My University, 2005)
A new CMOS OTA-based circuit is proposed to realize electronically tunable positive and negative floating resistors. The circuit employs two balanced OTAs and one fully differential OTA. The value of realized resistance can be linearly controlled by an external DC bias current over the range of more than 3 decades. The performances of the proposed circuit are discussed and confirmed through PSPICE simulation. © 2005 IEEE.
Keywords: CMOS OTA; Electronically tunable Resistor; Floating Resistor